2016
DOI: 10.1002/mds.26698
|View full text |Cite
|
Sign up to set email alerts
|

Vascular disease and vascular risk factors in relation to motor features and cognition in early Parkinson's disease

Abstract: ObjectiveThe purpose of this study was to examine the relationship between vascular disease (and vascular risk factors), cognition and motor phenotype in Parkinson's disease (PD).MethodsRecently diagnosed PD cases were enrolled in a multicenter prospective observational longitudinal cohort study. Montreal cognitive assessment (normal >23, mild cognitive impairment 22 to 23 or lower but without functional impairment, and dementia 21 or less with functional impairment) and Movement Disorder Society Unified PD Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
119
5
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(145 citation statements)
references
References 43 publications
19
119
5
2
Order By: Relevance
“…18,19 Finally, the positive test result in 1 control subject remains unexplained, as detailed review of this subject's clinical chart did not reveal any signs of prodromal parkinsonism. Although all VaP patients had unambiguous vascular magnetic resonance imaging abnormalities combined with a clinical presentation suggestive of VaP (eg, lower body parkinsonism), we cannot exclude that these patients had a mixed α-synucleinopathy and vasculopathy, as described previously for PD patients.…”
Section: May 2019mentioning
confidence: 90%
“…18,19 Finally, the positive test result in 1 control subject remains unexplained, as detailed review of this subject's clinical chart did not reveal any signs of prodromal parkinsonism. Although all VaP patients had unambiguous vascular magnetic resonance imaging abnormalities combined with a clinical presentation suggestive of VaP (eg, lower body parkinsonism), we cannot exclude that these patients had a mixed α-synucleinopathy and vasculopathy, as described previously for PD patients.…”
Section: May 2019mentioning
confidence: 90%
“…For example, cerebrovascular disease plays a part in the pathogenesis of PD 52 , the second most common neurodegenerative disorder, which is characterized by accumulation of α-synuclein and degeneration of dopaminergic neurons in the substantia nigra. Vascular disease and vascular risk factors aggravate motor dysfunction and cognitive impairment in PD 59 . Cerebrovascular disease, BBB impairments and neurovascular abnormalities are also found in HD 60,61 , an autosomal-dominant neurodegenerative disease with motor, cognitive, psychiatric, and metabolic abnormalities caused by the aggregation of mutant huntingtin protein.…”
Section: Vascular Pathology In Neurodegenerationmentioning
confidence: 99%
“…To date, 3 important trials, the Multidomain Alzheimer Preventive Trial, the Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability, and the Dutch Prevention of Dementia by Intensive Vascular Care trial, have shown somewhat variable results but suggest that targeting interventions to individuals at increased risk for dementia might be effective . The evidence that patients with PD have a higher incidence of vascular risk factors and cerebrovascular disease is limited, but there is reason to believe that those patients with this combination have a greater occurrence of certain levodopa‐resistant features such as cognitive decline and axial motor dysfunction even in the early clinical stages of the disease . Furthermore, statin therapy was found to be underutilized in those with high or medium cardiovascular risk (60% of recent‐onset patients in one study from Scotland), thus not only increasing the threat of vascular morbidity and mortality but also potentially accentuating cognitive and motor features associated with their disease.…”
Section: Targets For Disease Modificationmentioning
confidence: 99%